Metabolic syndrome and polycystic ovary syndrome - Sobstyl, Małgorzata; Tkaczuk-Włach, Joanna; Sobstyl, Jacek; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
The consequences of PCOS are the subject of constant research, yet a number of scientific reports underline the fact that in women with PCOS, there appear higher risk of glucose intolerance and diabetes type 2, hypertension, dislipidemia and atherosclerosis. The effects of PCOS reach beyond women’s reproductive axis. Metabolic syndrome occurs in 43-46% of patients with PCOS, which constitutes two times more than in women population. Insuline resistance and hyperinsulinemia are key disorders in both syndromes. Obesity, gestational diabetes, positive family history of diabetes type 2 and metabolic syndrome constitute a risk factor for metabolic disorder development in patients with PCOS. Farmacological treatment of PCO syndrome depends on dominating symptoms and patient’s current needs taking into account her reproductive status. For a long time, medicines which reduce insuline resistance have been used to treat PCOS, in ovulation stimulation as well as in improvement of metabolic disorders. Insuline sensitivity improvement via reduction of body weight (diet, physical exercises) and choosing active lifestyle appears to be a standard.